Missional metanoia: Missional spirituality in holistic theological education - Niemandt, Doret (HTS teologiese studies, 2021)
Theological education is in crisis having lost an important dimension with its main focus on quality academics often abstracted from real life. This study aimed to propose that the formation of spirituality is fundamental to theological education and that theological education should be a holistic formation. The setting of this study is re-imaging theological education in the Dutch Reformed Church (DRC), a denomination in the process of missional transformation, but it is also applicable to theological education in general. This study focused on the relation between theology and spirituality, the significance of missional spirituality in theological education and a probable model for the formation of a missional spirituality. The study found that theology and spirituality are interdependent, and theological education should thus focus on all the different areas of learning and formation, that is, minimum knowledge base, pass-on-able habits and skills, and attitudes and beliefs. Theological education should ultimately cultivate a missional spirituality, forming missional leaders for the church. Leaders who are equipped are able to equip others for God’s mission. Theological education is not about obtaining a degree but in essence a process of formation and transformation. Wright asks: if the gospel is not transforming you, will it transform anything else? Transformation to be able to transform – a missional metanoia.Contribution: This study provides a probable model for holistic theological education and the formation of a missional spirituality.